2003
DOI: 10.1007/s00234-003-1016-y
|View full text |Cite
|
Sign up to set email alerts
|

Zonal frequency analysis of infarct extent. Part II: Anterior and posterior cerebral artery infarctions

Abstract: The object of the study was to test the hypotheses that analysis of the anatomic zones affected by single anterior (A), posterior (P), and middle (M) cerebral artery (CA) infarcts, and by dual- and triple-vessel infarcts, will disclose (i) sites most frequently involved by each infarct type (peak sites), (ii) sites most frequently injured by multiple different infarct types (vulnerable zones), and (iii) anatomically overlapping sites in which the relative infarct frequency becomes equal for two or more differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It does not have a wedge shape with the apex pointing at the occipital horn and the base spreading to the superficial cortex as seen in the traditional depictions of the posterior borderzone [3, 9, 15, 28]. Because the template by Naidich et al [25,26,27] presented data mainly on infarcts surrounding the parasagittal area, comparison with our map was not possible. In the upper slices these investigators showed that the inferior parietal and part of the superior parietal lobules were infrequently involved by borderzone infarcts.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…It does not have a wedge shape with the apex pointing at the occipital horn and the base spreading to the superficial cortex as seen in the traditional depictions of the posterior borderzone [3, 9, 15, 28]. Because the template by Naidich et al [25,26,27] presented data mainly on infarcts surrounding the parasagittal area, comparison with our map was not possible. In the upper slices these investigators showed that the inferior parietal and part of the superior parietal lobules were infrequently involved by borderzone infarcts.…”
Section: Resultsmentioning
confidence: 86%
“…There has been surprisingly little discussion about the size of the ‘traditional’ borderzone region in the maps created by previous investigators [3, 9, 15, 17,25,26,27,28]. We examined whether the size of the rim around each infarct affected our findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is the presumed site of the borderzone between the territories of the anterior and middle cerebral arteries (ACA and MCA). The internal borderzone is the white matter region surrounding the centrum semiovale (Bogousslavsky and Regli, 1986;Donnan et al, 2002;Naidich and Brightbill, 2003;Naidich et al, 2003aNaidich et al, , 2003bTorvik, 1984;Wodarz, 1980;Zulch and Hossmann, 1989).…”
Section: Regions Of Interestmentioning
confidence: 99%
“…studies, some predating modern perfusion and magnetic resonance imaging (MRI); some were based on autopsies remote from the stroke event [2][3][4][10][11][12][13][14][15] or studies which used arterial template to infer infarct territory. 16 These prior studies, undertaken poststroke, have provided little information on the topography at stroke onset, the impact of collateral systems in modifying the arterial territory and the effect of this transformed territory on motor outcome.…”
mentioning
confidence: 99%